Synthesis, characterization, and analysis of zinc oxide nanoparticles using varying pulsed laser ablation energies in liquid - Tahani H. Flemban (Journal of Experimental Nanoscience)
Nanoparticles (NPs) find widespread applications in detectors, catalysis, optoelectronics, and medical devices, owing to their high surface-to-volume ratio and zero-dimensional confinement. However, addressing environmental concerns is crucial during the creation of novel nanostructured materials. Herein, ZnO NPs of different sizes were prepared via the pulsed laser ablation in liquid (PLAL) method at energies of 70, 90, and 130 mJ. The morphology and structural properties of the synthesized NPs were characterized by scanning electron microscopy, energy-dispersive X-ray spectrometry, and transmission electron microscopy. zeta-sizer and zeta-potential were used to ensure the physical stability of NPs. UV-Vis spectrophotometry measurement showed a blue shift in the band gaps with an increase in the pulsed laser energy leading to a decrease in the size of the NPs. Fourier-transform infrared spectroscopy technique confirmed the formation of ZnO NPs.